2022
DOI: 10.1021/acs.jafc.2c01329
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic Effect of Selenium on Fumonisin B1 Promotes Neutrophil Extracellular Traps Formation in Chicken Neutrophils

Abstract: Neutrophils are an important component of the innate immune system, and one of their defense mechanisms, neutrophil extracellular traps (NETs), is a hot topic of the current research. This study explored the effects of fumonisin B1 (FB1) on chicken neutrophil production of NETs and its possible molecular mechanism of action. Scanning electron microscopy and fluorescence microscopy were used to observe morphological changes in neutrophils, and a fluorescence microplate reader was used to detect reactive oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Previous studies have shown that Se antagonizes mycotoxin-induced immune suppression in vitro. Dietary supplements containing Se are primarily derived from inorganic sources, wherefore 0.2 mg/kg BW Na 2 SeO 3 was selected for this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that Se antagonizes mycotoxin-induced immune suppression in vitro. Dietary supplements containing Se are primarily derived from inorganic sources, wherefore 0.2 mg/kg BW Na 2 SeO 3 was selected for this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, the method of oral SeNP administration is used in studies on the influence of the source of Se on the functions of immune cells ([ 18 , 27 , 28 , 48 ] and many others). On the other hand, injections are also used to avoid loss and settling of highly reactive SeNPs in the digestive tract.…”
Section: Discussionmentioning
confidence: 99%
“…Fumonisin B1 has been shown to inhibit zymosan-induced NET formation in chicken neutrophils, preventing ROS burst and release of histone H3 and neutrophil elastase (NE). The addition of Se reduces the toxic effects of fumonisin B1 and restores NET formation, indicating that Se could be used as a potential drug to prevent fumonisin B1 toxicity in livestock [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fumonisin B1 (FB1) is a carcinogenic mycotoxin that is present in food and can cause health threats to animals or humans [ 48 50 ]. Yu et al developed a colorimetric assay for the detection of FB1 (Fig.…”
Section: Introductionmentioning
confidence: 99%